2021
DOI: 10.1371/journal.pone.0244838
|View full text |Cite
|
Sign up to set email alerts
|

The contributions of focused attention and open monitoring in mindfulness-based cognitive therapy for affective disturbances: A 3-armed randomized dismantling trial

Abstract: Objective Mindfulness-based cognitive therapy (MBCT) includes a combination of focused attention (FA) and open monitoring (OM) meditation practices. The aim of this study was to assess both short- and long-term between- and within-group differences in affective disturbance among FA, OM and their combination (MBCT) in the context of a randomized controlled trial. Method One hundred and four participants with mild to severe depression and anxiety were randomized into one of three 8-week interventions: MBCT (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…Because "the same treatment can have both beneficial and harmful effects" (Dimidjian & Hollon, 2010, p. 22), it is important to consider the balance between benefits and harms in clinical decision-making. For example, in the current study, clinically relevant events associated with impaired functioning occurred within a context of overall efficacy on multiple outcomes (Cullen et al, 2021), high practice compliance, and low attrition, which suggests that participants found the difficulties worth tolerating in light of expected or concurrent benefits or in comparison with not receiving treatment.…”
Section: Limitationsmentioning
confidence: 70%
See 2 more Smart Citations
“…Because "the same treatment can have both beneficial and harmful effects" (Dimidjian & Hollon, 2010, p. 22), it is important to consider the balance between benefits and harms in clinical decision-making. For example, in the current study, clinically relevant events associated with impaired functioning occurred within a context of overall efficacy on multiple outcomes (Cullen et al, 2021), high practice compliance, and low attrition, which suggests that participants found the difficulties worth tolerating in light of expected or concurrent benefits or in comparison with not receiving treatment.…”
Section: Limitationsmentioning
confidence: 70%
“…In terms of overall treatment efficacy, all three forms of mindfulness training produced large effect size improvements in IDS-C scores from baseline to posttreatment (ds = 1.48-1.65) and Week 20 follow-up (ds = 1.34-1.57) with no differences between groups (Cullen et al, 2021).…”
Section: Treatment Efficacymentioning
confidence: 90%
See 1 more Smart Citation
“…The current review may not be exhaustive, as SRPs are often measured as secondary outcomes and thus some important studies may not have been identified in this map. In addition, this review investigated the effects of meditation practice on SRPs without differentiating the types of meditation practices, which may impact target engagement and target validation ( Cullen et al, 2021 ). Additionally, our review depended on the measurement tools used in extant research, which have some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the field is witnessing the introduction of a quickly growing number of new self-report measures purported to more adequately capture already established constructs or to capture new constructs for meditation research (see Van Dam et al, 2018). Third, new and modified meditation-based programmes are increasingly complex, combining multiple practice modalities each targeting specific psychological capacities (e.g., Cullen et al, 2021;Goldberg et al, 2020). Importantly, the evaluation of the efficacy of these programmes will be affected by methodological decisions regarding the measurement of meditation-related mechanisms (e.g., data-driven vs. theory-based approaches, established scales vs. new scales).…”
Section: Future Directions: Conceptual and Methodological Considerationsmentioning
confidence: 99%